AUDITORÍA DE GESTIÓN AL DEPARTAMENTO FINANCIERO DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO DEL CANTÓN PALTAS DEL PERÍODO 2017 - ARMIJOS SOTO., JANDRY RONEY (2019)
This thesis called "AUDIT OF MANAGEMENT TO THE FINANCIAL DEPARTMENT OF THE DECENTRALIZED AUTONOMOUS GOVERNMENT OF THE CANTON PALTAS OF THE 2017 PERIOD", has the purpose of evaluating the internal control and performance of the financial department through the application of the Audit of Management, allowing the same to verify the level of compliance with the legal provisions, regulations and other regulations in force, also has as its purpose the applicability of management indicators that help determine the degree of effectiveness, efficiency, quality and economy, with which the department performed its mandated tasks. In order to comply with all the phases of the audit, it was initiated as a first instance by knowing the entity and its operations, collecting information and general documentation on which the preparation of the institutional SWOT was based, after an analysis and gathering more documentation the audit program was elaborated in which the procedure to be followed for the execution phase was stipulated, in which the narrative and analytical cards applied to each subcomponent of the financial component were elaborated, each of these procedures is supported with its respective working papers, which applying the audit techniques and procedures, could obtain sufficient and pertinent evidence to support the auditor's opinions for subsequent issuance of the audit report, which will be integrated with comments 5 conclusions and recommendations, the latter of immediate and indispensable applicability, for or that the follow-up schedule will be made to said recommendations, thus completing the integral audit process in all its stages. Regarding the evaluation of internal control and the management of the Financial Department of the GAD of Paltas, it can be stated that a Multi- Year Plan has not been prepared to help determine an adequate operational and budgetary planning, in addition to the absence of State Audit. Financial data to the GADP, which causes financial information to lack credibility and uncertainty in administrative decisions. At the conclusion of this thesis and in compliance with the audit process, the respective audit report is issued, detailing the main findings and weaknesses of the GAD Finance Department of Paltas in the respective comments and conclusions, in addition to these the respective recommendations are issued to help to solve said problems and shortcomings found, they are of importance and immediate applicability by the Municipality to ensure that its management line is directed to the adequate compliance of the strategic planning.